Prostori neskladij Etnografija prostora in kraja v vasi Dhërmi/Drimades, Južna Albanija - Gregorič Bon, Nataša (ZRC SAZU, Založba ZRC, 2008)
This monograph is about the ongoing, unstable reconstruction of spaces and places in the village of Dhërmi/Drimades of southern Albania. It is based on twelve months of anthropological field research in that village. Particular consideration is given to the process of reconfiguration and redefinition of the meanings that pertain to the village and its people. The monograph focuses on local peoples' biographies, oral histories, rhetorical claims, and their everyday discourses, through which it is shown how the meanings of the village are reconstructed through interrelations of the locals with other people and places. The underlying theme is the continuity of movements and interrelations through which the local people of Dhërmi/Drimades recreate and reproduce the sense of locatedness of "their" village and themselves.